A cross-country analysis of total factor productivity using micro-level data - Murat Seker; Federica Saliola (Central Bank Review (CBR), 2018)
Total factor productivity (TFP) is a crucial measure of efficiency and thus an important tool for policymakers. However, research on comparison of TFP performances using micro-level data across developing countries has been limited due to the unavailability of homogenous data sources. This study aims to fill this crucial gap by using a data set which has been collected through a large body of surveys conducted across 69 developing countries following the same methodology. The homogenous nature of the data and the diverse set of questions included in the surveys provide unique opportunity to compare average productivity performances of firms across a large set of characteristics and business environment factors. The analysis performed here provides the groundwork for testing various stylized facts about TFP and its related factors such as exporting, innovation, access to finance, foreign ownership, and regulations across developing countries.
Keywords: 330; Total factor productivity; Developing countries; Firm-level analysis; Cross-country comparison